2009
DOI: 10.1161/strokeaha.108.536698
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol LDL and 90-Day Mortality in Patients With Intracerebral Hemorrhage

Abstract: Background and Purpose-Prognostic significance of low-density lipoprotein cholesterol (LDL-C) in intracranial hemorrhage (ICH) is unclear. The objective of this study was to determine the association between LDL-C and mortality in ICH. Methods-Consecutive patients (nϭ88) presenting with ICH were included in the study. Lipid profile was obtained during the first hours after admission. We analyzed the impact of LDL-C on 90-day mortality using the Hazard Rate (HR) crude, analysis crude for trend by Mantel-Haensze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 12 publications
(14 reference statements)
1
34
0
Order By: Relevance
“…[1][2][3] Similarly, Bang et al's retrospective study reported a relationship between recanalization therapy, low cholesterol, and hemorrhagic infarction 15 while low LDL levels were reported by some as associated with hemorrhagic transformation after large artery stroke 16 or increased mortality in ICH. 17 The investigators in the SPARCL trial, however, found no relationship between ICH risk and low-density lipoprotein or total cholesterol levels. 13 The mechanism by which statin increases ICH risk could also be independent of its lipid-lowering effect and may be related to its pleiotropic and antithrombotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Similarly, Bang et al's retrospective study reported a relationship between recanalization therapy, low cholesterol, and hemorrhagic infarction 15 while low LDL levels were reported by some as associated with hemorrhagic transformation after large artery stroke 16 or increased mortality in ICH. 17 The investigators in the SPARCL trial, however, found no relationship between ICH risk and low-density lipoprotein or total cholesterol levels. 13 The mechanism by which statin increases ICH risk could also be independent of its lipid-lowering effect and may be related to its pleiotropic and antithrombotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, available evidence from clinical trials suggests a link between statin use and increased risk of recurrent ICH. 24 While the lipid-lowering effect of statins could explain their detrimental long-term effect on ICH risk, we did not identify interactions between cholesterol levels and short-term benefit on functional outcome.…”
Section: Statin Use and Neuroimaging Predictors Of Ich Outcomementioning
confidence: 99%
“…[2][3][4] Other studies have, on the contrary, found statins to be associated with reduced disability and mortality after ICH. 5,6 Also low serum cholesterol, 7 low-density lipoprotein (LDL) cholesterol, [7][8][9][10] and triglyceride levels 7 were associated with an increased risk of ICH and ICH mortality, although not in all studies. 4 Because of these controversial results, we decided to study the associations of premorbid statin usage and baseline lipid profiles on the functional outcome and mortality in consecutive ICH patients.…”
mentioning
confidence: 98%